Thrombocytopenia in patients diagnosed with Malaria in District Buner, KP - Noor Muhammad , Muhammad Hammad Khan , Hafiza Ayesha Jawaid , Syed Mohsin Ali Shah , Muhammad Owais Ali , Ayesha Sher Khan, Noor Muhammad , Muhammad Hammad Khan , Hafiza Ayesha Jawaid , Syed Mohsin Ali Shah , Muhammad Owais Ali , Ayesha Sher Khan (Journal of Rawalpindi Medical College, 2020)
Introduction: Thrombocytopenia is one of the numerous complications of malaria infection, which could be lethal if not diagnosed and managed on time. Our study aims to determine the occurrence of thrombocytopenia in patients hospitalized with malaria. Material and Methods: A retrospective cross-sectional study was conducted between January 2016 till December 2019. Data was collected from the patient’s record registers. A total of 201 cases were included in this study. Data was collected, entered, and analyzed in IBM SPSS 23 software package. Results: Out of the total 201 cases, 108 (53.7%) were males and 93 (46.3%) were females. 189 (94%) cases were suffering from P. vivax, 10 (5%) were suffering from P. falciparum, and cases suffering from both were only 2 (1%). Thrombocytopenia was present in 183 (91.04%) cases (95% confidence interval 2.13-2.37). 91.53% (n=173) of cases diagnosed with P. vivax had thrombocytopenia while 90% (n=9) cases diagnosed with P. falciparum had thrombocytopenia. Conclusion: We conclude from this study that, thrombocytopenia occurs in all species of malaria and is not a distinguishing feature between the principal types of malaria. With prompt identification and management, platelets count reverts back to normal.